Bifidobacteria : important roles in the medical aspects - Sookkhee, Siriwoot (Biomedical Sciences and Clinical Medicine, 2024)
Bifidobacteria is one of probiotics, a microorganism that possessed the benefit effects to health of human. It is predominantly in fecal flora of mother milk-drinking infant. The popular species in this genus are B. bifidum, B. infantis, and B. lactis which used in fermented milk. After reviewed the literatures, it could be reported to the reduction of transit time in gastrointestinal tract, constipation, and irritable bowel syndrome. The bacteria can ferment lactose and results to decrease the amount of intestinal lactose and lactose intolerance in infant. The bacteria can produce the antimicrobial compounds such as organic acid and bacteriocins. Moreover, it can also induce the productions of cytokine and chemokine for moderate host immunity and protect the infection. From the clinical trials, its beneficial effects were reported for the prevention and decrease of rotavirus-infected diarrhea, antibiotic-associated diarrhea, inflammatory bowel disease and the protection of bile salt toxicity. This review supports the idea to apply this bacteria for the further formulation of medical products.